2007
DOI: 10.1038/bdj.2007.79
|View full text |Cite
|
Sign up to set email alerts
|

Provision of domiciliary dental care by Scottish dentists: a national survey

Abstract: Staff training, specialist equipment and new service models for the delivery of domiciliary care are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…All studies retrieved were representative for Western countries: Canada , Germany , Belgium , Scotland , New Zealand and Australia . The barriers experienced in these countries are almost identical, and the percentage of older patients does not vary much 14% (New Zealand/Australia) and 21% (Germany) (http://www.indexmundi.com; http://www.sdi.co.uk).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies retrieved were representative for Western countries: Canada , Germany , Belgium , Scotland , New Zealand and Australia . The barriers experienced in these countries are almost identical, and the percentage of older patients does not vary much 14% (New Zealand/Australia) and 21% (Germany) (http://www.indexmundi.com; http://www.sdi.co.uk).…”
Section: Discussionmentioning
confidence: 99%
“…Table 3. Sample of dentists and number of participating dentists of the studies described in the publications included in the review Article Sample of dentists Number and percentage of participating dentists MacEntee et al, (22) 603 334 (55%) Nitschke et al, (23) 8588 180 (2%) De Visschere and Vanobbergen, (24) 673 101 (15%) Sweeney et al, (21) 2060 1359 (66%) Antoun et al, (25) 677 437 (65%) Hopcraft et al, (26) 213 122 (57%) Chowdhry et al, (27) 800 251 (31%)…”
Section: Studies Included In Chronological Ordermentioning
confidence: 99%
“…The Ministry of Health, Labour and Welfare has implemented various projects aimed at healthcare integration and has revised medical fees in order to promote home dental care. Studies on domiciliary dental care in the elderly have been conducted in Finland 4) , Scotland 7) and Belgium 2) ; a number of studies on this issue have also been conducted at universities in the United States 6) . Dental instruments used in domiciliary care have also been studied 1) .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of regional factors, the present study showed that a lack of neighborhood dental clinics providing domiciliary dental care was a barrier to receiving domiciliary dental care. A lack of dentists who supplied domiciliary dental care has also been reported in other countries, particularly as this represents a high‐cost, time‐consuming service, dental equipment suitable for home service was lacking, and dentists were poorly trained for home care …”
Section: Discussionmentioning
confidence: 87%